Characterization of meningococcal serogroup B outer membrane vesicle vaccines from strain 44/76 after growth in different media. - Tsolakos, N; Lie, K; Bolstad, K; Maslen, S; Kristiansen, P; Høiby, E; Wallington, A; Vipond, C; Skehel, M; Tang, C; Feavers, I; Wedege, E; et al. (2010)
In this study, we evaluated the effect of the growth medium on the composition and immunogenicity of meningococcal outer membrane vesicle (OMV) vaccines after cultivation of the Norwegian serogroup B 44/76 vaccine strain in either Frantz' or modified Catlin-6 media (MC.6M). Differential proteomic analysis revealed that 97% of the OMV proteins maintained the same levels in the two preparations. However, a number of differentially expressed proteins, including TdfH, OpcA, OMP NMB0088, hypothetical NMB2134, lipoprotein NMB1126/1164 and NspA, increased significantly in OMVs produced from bacteria grown in the MC.6M. Together with increased lipopolysaccharide levels, the increased expression of these proteins was associated with significantly higher serum bactericidal titres in mice immunized with the MC.6M OMV vaccine. The high resolution two-dimensional separation of the OMVs on a large-format gel across a pH range of 3-11 resolved around 2000 protein spots from which 75 proteins were identified by mass spectrometry.